APPLICATION OF BUSINESS ADMINISTRATION COOPERATION SERBA KARYAMANDIRI - Guruh Edi Putra (Jurnal Sistem Informasi, 2007)
In writing this author tries to help Seraba Cooperative Enterprises Karya Mandiri in performing calculations and preparing reports SHU, by creating a database application. Expected apliksi can accelerate and simplify the calculations and preparing reports. Data storage - data is stored using hard disk media as a storage file so it reduced the use of books and can find data quickly and efficiently as well as recording transactions. The report in this application can display the data - data that is required as the transaction data, the data members' savings, borrowing data members. With this report is expected to provide appropriate information and quick to Treasurer cooperatives.